Research on Realization of MSE Equipment Based on OpenFlow Protocol - Yongqing Zhu; Huanan Chen; Hong Tang (Dianxin kexue, 2013)
The theory of OpenFlow and MSE equipment were deeply and widely discussed. On the basis of the research, the MSE implementation with the extension of the OpenFlow protocol was proposed. It is a feasible solution for the IP network evolving to the SDN architecture.